2014
DOI: 10.1038/sc.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Use of screening to recruitment ratios as a tool for planning and implementing spinal cord injury rehabilitation research

Abstract: Having acknowledged these valuable contributors, the authors remain fully and solely responsible for the report and its contents.Please address comments and correspondence concerning this report to info@rickhanseninsti tute.org, with "Incidence and Prevalence Report" in the subject line. D e c e m b e r 2 0 1 0This report may be reproduced in whole or in part with appropriate acknowledgement of the source. U R B A N F U T U R E SS S t t r r a a t t e e g g i i c c R R e e s s e e a a r r c c h h t t o o M M a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Measures to minimize participant drop out should be incorporated in future trial designs. The high attrition rate in this study, although comparable to SCI cohort research 39 and internet-based interventions, 40 was characterized by a subset of individuals who reported diagnostic symptoms consistent with a depressive disorder (PHQ > 10). Future research might only enrol participants most likely to complete the study, determined by baseline mood status, although this then limits the generalizability of the findings to those who are symptomatic.…”
Section: Discussionmentioning
confidence: 70%
“…Measures to minimize participant drop out should be incorporated in future trial designs. The high attrition rate in this study, although comparable to SCI cohort research 39 and internet-based interventions, 40 was characterized by a subset of individuals who reported diagnostic symptoms consistent with a depressive disorder (PHQ > 10). Future research might only enrol participants most likely to complete the study, determined by baseline mood status, although this then limits the generalizability of the findings to those who are symptomatic.…”
Section: Discussionmentioning
confidence: 70%
“…Five individuals did not respond following initial contact, four individuals did not meet the inclusion criteria, and one individual declined to participate due to concerns regarding time commitment. A 2:1 screening to recruitment ratio for SCI rehabilitation interventions (43) has been reported, which may explain our small sample. We reported a 3:1 screening to recruitment ratio for this study.…”
Section: Discussionmentioning
confidence: 87%
“…The comparison of participation rates between studies turns out to be futile as a result of how differently recruitment, screening and participation rates have been determined and the various recruitment and screening procedures. For instance, Craven et al 9 have reported the screening to recruitment ratio for different study designs and intervention types (ranging from 5:1 to 2:1). The ratio was calculated by dividing the number of consenting patients who underwent screening by the number of eligible patients enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%